Comparison of the Otto Bock solid ankle cushion heel foot with wooden keel to the low-cost CR-Equipements™ solid ankle cushion heel foot with polypropylene keel: A randomized prospective double-blind crossover study assessing patient satisfaction and energy expenditure. (June 2017) - Lacraz, Alain; Armand, Stéphane; Turcot, Katia; Carmona, Gorki; Stern, Richard; Borens, Olivier; Assal, Mathieu
Background: The International Committee of the Red Cross supports a worldwide program of prosthetic fitting and rehabilitation. In this context, a prosthetic foot was developed and widely distributed in least developed countries. Study design: Prospective, randomized, double-blind, controlled study. Objective: To compare patient satisfaction and energy expenditure during ambulation between a low-cost prosthetic foot designed with a polypropylene keel (CR-Equipements ™ solid ankle cushion heel, International Committee of the Red Cross) to a well-recognized solid ankle cushion heel foot with a wooden keel (solid ankle cushion heel foot, Otto Bock). Methods: A total of 15 participants with unilateral transtibial amputation were evaluated using the two prosthetic feet in a randomized prospective double-blind crossover study. Main outcomes were patient satisfaction questionnaires (Satisfaction with Prosthesis Questionnaire and prosthetic foot satisfaction) and energy expenditure (oxygen consumption—mL/kg/min, oxygen cost—mL/kg/m, and heart rate—bpm). Results: There were no significant differences between the two prosthetic feet for satisfaction and energy expenditure. Conclusion: The low-cost solid ankle cushion heel foot with polypropylene keel provides comparable satisfaction and similar energy expenditure as the solid ankle cushion heel foot with wooden keel. Clinical relevance: The results of this study support the application and widespread use of the CR-Equipements ™ solid ankle cushion heel foot. From a cost-effectiveness standpoint, patients are well satisfied and exhibit similar outcomes at a substantially lower cost.